A COMPREHENSIVE REVIEW OF THE RECENT ADVANCEMENTS IN THE DEVELOPMENT OF A DENGUE VACCINE: IN THE HOUR OF NEED - Kevin, Emmanuel Suresh; John, Abraham; Clement, Prakash TJ; Anieta, Merin Jacob; Ambika, Akhoury (International Journal of Pharma and Bio Sciences, 2025)
Dengue fever, caused by the Dengue virus (DENV), remains a critical public health challenge, particularly in tropical and subtropical regions. Despite advancements in vaccine development, achieving an effective and universally safe vaccine remains complex due to the presence of four distinct serotypes (DENV-1 to DENV-4), which contribute to antibody-dependent enhancement (ADE) and inconsistent immune responses. Current vaccines, such as Dengvaxia, TAK-003 (QDENGA®), and TV003/TV005, demonstrate varying efficacy and safety profiles, necessitating further research into balanced immunity, reduced ADE risk, and global accessibility. This review aims to bridge the knowledge gaps present in existing literature by providing a comprehensive analysis of dengue vaccine development, challenges in implementation, and potential future strategies. It seeks to provide a detailed and updated analysis of the advancements in dengue vaccine development, identifying gaps in existing studies and highlighting strategies to overcome current challenges in achieving a safe and effective vaccine. The review includes an examination of the epidemiology and immunology of dengue fever and its impact on global health, an evaluation of the progress and limitations of existing dengue vaccines, including Dengvaxia, TAK-003, and TV003/TV005, an analysis of the challenges in vaccine development such as ADE, serotype-specific immunity, and accessibility in endemic regions, and a discussion of emerging vaccine platforms, including mRNA-based and vector-based approaches. Additionally, it proposes recommendations for future research and policy strategies for improved vaccine deployment and disease management. Through an exhaustive review of existing research, this article aims to contribute valuable insights to the scientific community, fostering further innovation in dengue vaccine development and public health strategies. Key words: Dengue Virus, Dengue Fever, Antibody Dependent Enhancement, Chimeric Yellow Fever-Dengue-Tetravalent Dengue Vaccine, Takeda, Antigen-Antibody, Cluster of Differentiation, Virologically Confirmed Dengue, Dengue Purified Inactivated Vaccine, Tetravalent Dengue DNA Vaccine.